Developing e-counselling system - Ahmad Dahlan, Abdul Rahman; Rahmat, Nur Atiqah Syakila; Mazlan, Maisarah (Research Publish Journals, 2015)
This paper introduces a Web-based Counselling System, a non-profit online counselling web portal that was built to provide a platform for counselors to reach out to the general public. We examine the background that induced the conceptualization of the portal, the system’s architecture and design as well as the implementation of the working system. The paper closes with an evaluation of the system. Counselling aim is to help a person to talk about emotions and thoughts that they may not have been able to express before, or address important matters they have put off, which always seems to return. Islam tells its followers to attain personal well-being through its system of spiritual and religiosity. This paper explore on how to council process of face boldly between professional counselors with client for make human affair, to identify self-potential and develop source of human internal for take as true and self-responsible toward Allah bless.